A liderança agregadora entre e com as pessoas numa gestão compartilhada - Correa, Ana Claudia (Universidade do Vale do Rio dos Sinos, 2023)
The research “the aggregating leadership among and with the people in a shared-management” presents reflections, analyses and a proposition regarding the aggregating leadership and shared-management in a private school, nominated for this research as Utopia school, in the city of Porto Alegre. In order to investigate and analyze two categories, it involved six managers from the referred school. The analysis concerned the following categories: a) aggregating leadership; b) shared-management; these categories guided the research as they are considered essential for the work carried out in an educational institution. The referred research relies on eight chapters that presented the specificities, such as: the research problem, the objectives, the contextualization, the state of knowledge, the theoretical framework, the methodology with the qualitative approach by means of the interpretative analysis of the data, based on the descriptive observations and questionnaire collected and finally the suggestion of an interventional proposal with the elaboration of a Study Plan. The reflexive contribution highlighted the necessity of an aggregating and shared educational management, committed to the democratic and emancipatory participation, creating spaces for systemic reflection and discussion in the institution, highlighting the necessity and the importance of the effectiveness of a work aimed at the continuing and permanent training in the school environment as a proposal for intervention.
Keywords: Liderança agregadora; Gestão compartilhada; Participação democrática; Diálogo; Reflexão; Aggregating leadership; Shared-management; Democratic participation; Dialogue; Reflection; ACCNPQ::Ciências Humanas::Educação